"Still a bit uncomfortable, to be an arm of the state": Making sense and subjects of counter-extremism in the UK and Morocco. (March 2022) - Bastani, Niyousha; Gazzotti, Lorena
Countering violent extremism (CVE) policies infiltrate every corner of public life, travelling across the Global North and South. However, scholars have under-analysed the perspective of those charged with CVE's implementation, and have treated CVE in a spatial binary, implying that its operationalisations in the Global North and South are conceptually distinct. This article presents a comparative political ethnography of CVE projects framed as care provision in the field of education in Morocco and the UK. It asks, how is CVE rationalised for and by non-traditional security actors in education, such as university and NGO administrators, and how is it integrated into the ordinary across the North and the South? In both contexts, implementation does not "just" enrol those involved with care duties at their institution into the government of the "dangerous other." It also shapes the self-governance of those transformed into hesitant security actors. This paper argues that implementers leverage the 'normal politics' of institutional care to implement the global counter-extremist agenda. CVE enters spaces of education globally through camouflage – it blends itself into existing understandings and practices of institutional care, whatever they may be. By working across the North and the South through similar mechanisms of sense and subject-making, CVE recruits implementers for the co-production of an expansive global geography of exclusion that locates marginalised young Muslims as global outsiders within.